Reform of The Criminal System In Mineral and Coal Mining Licensing Policies Oriented Towards Ecological Justice - Dannie Chaeruddin (Pelopor Publikasi Akademika, 2024)
Environmental damage due to the conversion of green land into uncontrolled mining areas is basically influenced by the issue of area allocation permits. Most of the RPJMD and the issuance of area allocation permits do not rely on the existing Regional Spatial Plan, in addition, the RTRW that is made often does not have clear certainty in terms of determining the zoning of the area allocation. The consequences of this ultimately result in various types of problematic mining business permit issuances and result in environmental damage, agrarian disputes, and the partialization of ecological justice. The threat of sanctions in the provisions of Article 165 as a medium to prevent mining permit crimes has in fact been abolished with the enactment of Law Number 3 of 2020 as an amendment to Law Number 4 of 2009 concerning Mineral and Coal Mining. This will clearly result in increasingly rampant criminal acts in the issuance of mineral and coal mining permits in Indonesia. This article uses a doctrinal research method, where the research conducted is research related to the analysis of the norms behind the text of laws and regulations, both legally and philosophically. Based on the study conducted, it can be seen that the implementation of sanctions in the issuance of deviant mineral and coal mining permits has not been able to realize fair legal justice, considering that the provisions of Article 165 of Law Number 4 of 2009 are not maintained in Law Number 3 of 2020, so that bureaucrats who make problematic mineral and coal permits cannot be subject to criminal penalties, either imprisonment or fines, then the threat of Article 165 of Law Number 4 of 2009 is relatively light when compared to the environmental damage caused by mineral and coal mining.